2014
DOI: 10.7860/jcdr/2014/8541.4567
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Awareness of Do’s and Don’ts of Cardiopulmonary Resuscitation Among University Medical Students-A Questionnaire Study

Abstract: Background: Medical students today are tomorrow's future doctors. One of the key skills that students should develop during their graduation training is to be prepared for emergency life saving measures like cardiopulmonary resuscitation (CPR) anytime, anywhere. The students play integral role in learning, mastering and inculcating the most pragmatic clinical skill of CPR.Objectives: a) To evaluate the CPR awareness among undergraduate medical students. b) To screen the knowledge regarding accurate, effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Most of the nursing students in this study had less subjective norms about being bystander CPR. This was different from a previous study which mentions that health worker tends to have good subjective norms about CPR because they are demanded by colleagues, senior, junior, and society to carry out their role ideally as a health worker in every action (Kumari et al, 2014). Subjective norms influenced by normative beliefs and motivation to comply which are defined as motivation to achieve the expectations of those around us both parents, friends, and people who have an important position in someone's life.…”
Section: Discussioncontrasting
confidence: 68%
“…Most of the nursing students in this study had less subjective norms about being bystander CPR. This was different from a previous study which mentions that health worker tends to have good subjective norms about CPR because they are demanded by colleagues, senior, junior, and society to carry out their role ideally as a health worker in every action (Kumari et al, 2014). Subjective norms influenced by normative beliefs and motivation to comply which are defined as motivation to achieve the expectations of those around us both parents, friends, and people who have an important position in someone's life.…”
Section: Discussioncontrasting
confidence: 68%
“…In Poland, BLS training was integrated within medical college curricula. In Saudi Arabia, 67.5% of health students in Princess Nourah University previously received BLS training courses [ 22 ]. This figure was higher in comparison to our figure.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to this finding, a study among health interns among different universities in Saudi Arabia reported that up to 70% of students suggested that BLS training should be included in their college curricula [ 23 ]. Various studies recommended including a BLS training course in the college curriculum, for early exposure to BLS experience [ 22 , 23 , 24 ]. These studies confirmed the importance and benefits of having BLS training at the university.…”
Section: Discussionmentioning
confidence: 99%
“…Kuesioner penelitian ini menggunakan kuesioner penelitian sebelumnya yang sudah dilakukan oleh Meena Kumari dkk 9 pada tahun 2014 di India. Kuesioner dibagi menjadi 3 bagian, dimana pada bagian 1, penilaian menggunakan pilihan iya atau tidak.…”
Section: Bahan Dan Metodeunclassified